2010
DOI: 10.1002/etc.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmentally relevant concentrations of endosulfan, azinphosmethyl, and diazinon on Great Basin spadefoot (Spea intermontana) and Pacific treefrog (Pseudacris regilla)

Abstract: We conducted dose-response exposures to compare the lethality of endosulfan, diazinon, and azinphosmethyl in the early-life stages of the Great Basin spadefoot (Spea intermontana) and the Pacific treefrog (Pseudacris regilla). Our experiment occurred in two 8-d phases: one, with developing embryos, and two, with Gosner Stage 27 tadpoles. Pesticide concentrations were representative of field-measured concentrations (60 ng/L of endosulfan, 50 ng/L of azinphosmethyl, and 350 ng/L of diazinon), in the same geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Bionda et al (2013) reported that amphibians in altered Argentinean agroecosystems had lower egg and larval survival compared with organisms from noncultivated area with population projections less favorable leading to extinction in crop-dominated areas. Several laboratory studies reported adverse effects of endosulfan on amphibian embryo-larval development, i.e., lethality in various species at environmentally relevant concentrations (Jones et al 2009;De Jong Westman et al 2010), delay to complete metamorphosis (Brunelli et al 2009), malformations of gills (Bernabó et al 2008), failures in the endocrine system (Goulet and Hontela 2003), and neurotoxic effects (Agostini et al 2009;Denoël et al 2013;Svartz et al 2014). However, most toxicity studies evaluate adverse effects under acute exposure condition only during certain periods of the life cycle.…”
mentioning
confidence: 98%
“…Bionda et al (2013) reported that amphibians in altered Argentinean agroecosystems had lower egg and larval survival compared with organisms from noncultivated area with population projections less favorable leading to extinction in crop-dominated areas. Several laboratory studies reported adverse effects of endosulfan on amphibian embryo-larval development, i.e., lethality in various species at environmentally relevant concentrations (Jones et al 2009;De Jong Westman et al 2010), delay to complete metamorphosis (Brunelli et al 2009), malformations of gills (Bernabó et al 2008), failures in the endocrine system (Goulet and Hontela 2003), and neurotoxic effects (Agostini et al 2009;Denoël et al 2013;Svartz et al 2014). However, most toxicity studies evaluate adverse effects under acute exposure condition only during certain periods of the life cycle.…”
mentioning
confidence: 98%